Genetic Background Heavily Impacts Effects of Diet on Obesity in a Collaborative Cross Population. (29th May 2020) - Yam, Phoebe; Albright, Jody; VerHague, Melissa; Bennett, Brian
Abstract: Objectives: Obesity is a complex disease long established to be strongly influenced by diet, yet it is still unclear why no specific diet can effectively control obesity development across all human populations. Because genetics also strongly impacts the development of obesity, we tested the hypothesis that individual genetic background determines how strongly diet affects adiposity accumulation by quantifying the impact of genetics and diet on adiposity in a panel of genetically diverse recombinant inbred mice. Methods: Female mice from 22 Collaborative Cross (CC) strains (total n = 204) were first placed on a synthetic control (AIN-76A) diet for 2 weeks, and then randomly assigned to either a high protein (HP, n = 102) or high fat high sucrose (HS, n = 102) diet for 8 weeks. MRI body composition analysis was performed on the mice to assess baseline body composition and weight after 2 weeks on AIN-76A, and again 8 weeks post-diet. Changes in adiposity accumulation (ΔBF%) were calculated by subtracting baseline % body fat (BF%) from post-diet BF%. Results: At baseline there was a wide range of adiposity in the CC ranging from 1.1–29.8% body fat, with line CC019 least susceptible to obesity (mean BF% = 4.4 ± 0.56%) and line CC028 most susceptible (mean BF% = 23.1 ± 1.5%); genetic background (CC strain) had a significant effect on BF% (ANOVA, F = 12.4, P = 7.7 × 10 −25 ). After 8 weeks of the diet challenge, CC019 was the strain least susceptible to obesity regardless of diet (mean HP BF% = 4.7 ± 0.4%, mean HS BF% = 4.6 ± 0.5%), while strains most prone to obesity on HP and HS diets were CC040 (mean BF% = 29.7 ± 1.3%) and CC028 (mean BF% = 35.7 ± 2.0%), respectively. Diet induced a wide range of effects on changes in adiposity depending on strain, including fat loss on both diets (CC036, ΔBF% HP = −5.1 ± 2.5% and HS = −4.1 ± 2.3%), similar fat gain on both diets (CC040, ΔBF% HP = 4.2 ± 0.8% and HS = 5.1 ± 2.1%), dramatic fat gain on one diet compared to the other (CC028, ΔBF% HP = 2.0 ± 1.1% and HS = 11.1 ± 1.1%), or fat loss/gain depending on the diet (CC027, ΔBF% HP = −1.4 ± 1.0% and HS = 6.8 ± 1.7%). Linear mixed model analysis revealed significant effects of strain x diet interactions on ΔBF% (Satterthwaite approx., P = 1.5 × 10 −5 ). Conclusions: Genetic background plays a significant role in the predisposition of obesity development and determining the degree of diet effects on adiposity accumulation in the CC. Funding Sources: USDA.